Citation of documentary sources and choice of informants: a qualitative study of the reasons given by venezuelan researchers - Arias Odon, Fidias Gerardo (2019)
The current investigation intends to interpret the reasons exposed by a group of researchers to cite and discard sources of live and documentary information. To achieve this goal, a study from a qualitative focus was carried out. Interviews and focal groups of discussion were used as techniques. The participants in the research were 12 active researchers, who provided the information based on their experience and subjective perception of reality. The results were contrasted with the reliability and quality criteria of the information sources exposed in the specialized literature. Among the most relevant findings, the coincidence in objective reasons of choice and the difference among the subjective reasons of each researcher stand out. Finally, some recommendations are presented for the selection of printed and digital sources, as well as for the choice of live sources (key informants and experts).